Informality in labor market and welfare - Sanches, Daniel Rocha (2005)
The neoclassical growth model with two sectors in production is employed in this paper in order to investigate how a change in the tax structure affects informality and welfare. We calibrate and simulate the model and find that welfare always increases when we reduce the tax rate on the demand for labor and adjust the tax rate on the value added so that the government revenue remains constant.